Boost enrollment with innovative approaches, teamwork. Issue 11 (10th January 2022) - Hope, Joan
Abstract : In fall 2021, Cornell College in Iowa enrolled its largest class in 18 years. A focus on recruitment and retention embedded in a new administrative structure resulted in that success at a time when many small liberal arts colleges are struggling with enrollment.